Hemogram Parameters and Hemogram-Derived Ratios in Covid-19 Severity - TOK, Duran; BAKIR, Fatih (Clinical Medicine And Health Research Journal, 2023)
Background: Understanding the hematological manifestations of the COVID-19, is of paramount importance in terms of patient management and prognosis. Aim: To review the fundamental hemogram parameters and their clinical significance. Methods: This is a retrospective, cross-sectional, and observational investigation. Hemogram findings of the participants within 30 days following the onset of symptoms were analyzed. Participants were categorized into moderate and severe groups based on the assessment of disease severity. Results: Both erythrocyte sedimentation rate and C-reactive protein are considerably elevated in both groups, with higher levels observed in the severe group compared to the moderate group. The percentage of neutrophils, is elevated above normal in both groups, with the severe group demonstrating higher values. The statistical difference between the groups is significant. Conclusion: Hemogram-derived ratios would be beneficial to include them in common laboratory practices.